Implementation of Compulsory Study 12 Year Policy to Increase Education Quality in Kudus Regency - Asih Widi Lestari; Andy Fefta Wijaya; Siti Rochmah (Wacana Journal of Social and Humanity Studies, 2015)
Education is an important instrument in improving the human resources quality. Kudus Regency has implemented compulsory study since 2010 through Kudus Regency Regional Regulation Number 2/ 2010 about Compulsory Study 12 (Twelve) Years. While, Central Government issued compulsory study 12 year policy in June 2013 through Ministry of Education and Culture Regulation Number 80/2013 about Universal Secondary Education. Obviously, this is a bold step of Kudus Regency Government in improving the education quality at Kudus Regency. The research objectives are: to know, analyze, and describe about Implementation of compulsory study 12 years policy to increase education in Kudus Regency; and to know, analyze, and describe about supporting and inhibiting factors toward implementation of compulsory study 12 years policy to increase education quality in Kudus Regency. This research resulted that the implementation compulsory study 12 years policy in Kudus Regency has been successfully, viewed from the actor that completely carry out their duties and responsibilities; the existence of funding and programs from Kudus Regency Government and Central Government is supporting the mechanism implementation in accordance with the provisions. The compulsory study 12 years policy in Kudus Regency had positive impact in improving the education quality at Kudus Regency, it is seen from the increase of Gross Enrollment Ratio (GER) for secondary education from 60% in 2008 to 80,59% in 2013. The success in improving the education quality is also seen from achievement of Kudus Regency in obtained champions in various championships. The supporting factors are The content of the Kudus Regency Regional Regulation Number 2/ 2010 about Compulsory Study 12 Years and the Minister of Education and Culture Regulation Number 80/ 2013 about Universal Secondary Education which clear and easy to understand; the willingness of Kudus Society in receiving the compulsory study 12 years policy; the support funding and scholarships provided by Kudus Regency Government and Central Government. And the inhibiting factors are lack of quality and quantity of human resources (teachers) in Kudus Regency; lack of facilities and infrastructure in supporting the education; the facilities and infrastructure referred is the practice equipments for students that expensive; inequality in educational development at Kudus Regency, especially in rural area; the mindset of Kudus Regency society who ignore the education, especially in rural area; unpredictable conditions such as flood that rather frequently in Kudus, so that damage the education infrastructure.Â Keyword: Compulsory Study 12 Year Policy, Education Quality, Kudus Regency